Assessment of economic security of households based on a scenario analysis - Marek Kośny; Maria Piotrowska (Economies, 2019)
The article proposes a method to assess the level of economic security, based on the analysis of scenarios of future events. These scenarios cover realistically possible combinations of future events, both positive and negative, allowing for an assessment of their financial implications. The empirical part of the paper contains the results of applying the proposed method to the Polish data. In the scenarios considered, changes in the situation of individuals in the labour market and changes in the level of income and expenditure are taken into account.
Keywords: D19; D31; I31; 330; economic security; economic stability; income; savings; scenario analysis